Ethnicity, Religion, Race, and Inter-group Relations Elements in Campaign: A Comparative Study of North Sumatra and Jakarta Election (Law Research Review Quarterly, 2018)
Election of regional heads in Indonesia is currently held more than 300 regions both provincial and city. Based on Article 56 of Law Number 32 Year 2004 concerning Regional Government, it is stated that the Regional Head and Deputy Regional Head are elected in a pair of candidates which are carried out democratically based on the principle of direct, general free, secret, honest and fair. This paper aims to examine the elements of SARA (Ethnic, Religious, Racial, and Intergroup) in regional election campaigns in DKI Jakarta and North Sumatra. The campaign is a space that voters must use to evaluate the vision, mission and program of election participants. But in reality the SARA element is often used as a stepping stone in campaigning. The important point in this paper is to find out what factors are behind the SARA element in campaign activities. Does the SARA element in the campaign have an influence on voter votes? Or apparently not? The types of SARA elements favored in the campaigns in DKI Jakarta and North Sumatra are certainly different, in terms of the type of SARA used, the attitude of the people in the area and how the SARA elements are used in the campaign. The use of religious and ethnic identity has been seen as getting stronger since 2014 after the influence of lying news circulating on social media such as Facebook, Whats App, BBM and Instagram.